CYTOTOXIC ACTIVITY OF SELECTED LIBYAN MEDICINAL PLANTS ON HUMAN BREAST ADENOCARCINOMA CELL LINE (MCF-7) - Jamal, Elmezogi; Gazala, Ben Hussien; Mabrouk, Erhuma; Manal, Gadmour; Abdulmotaleb, Zetrini; Abossa, Abdolgader; Shilpi, Jamil Ahmad (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
Three Libyan plants namely Ballota pseudodictamnus, Hedera helix, Thapsia garganica were tested for anticancer activity. The plants, collected from Aljabal-Al-Akhdar area of Libya in April 2010 were shed dried and subjected to Soxhlet extraction by methanol. Phytochemical screening indicated the presence of 2-deoxy sugars, flavonoids, saponins and tannins but absence of alkaloids in all three plants under investigation. Antiproliferative activity was performed breast adenocarcinoma cell line (MCF7). At the concentration of 100µg/mL, B. pseudodictamnus, T. garganica and H. helix showed 90, 60 and 5% cell death, respectively as compared to the control. Key words: Antiproliferative; Breast adenocarcinoma; Cell l ine MCF-7